A New Augmentation Method for Improved Screw Fixation in Fragile Bone - Raina, Deepak Bushan; Markevičiūtė, Vetra; Stravinskas, Mindaugas; Kok, Joeri; Jacobson, Ida; Liu, Yang; Sezgin, Erdem Aras; Isaksson, Hanna; Zwingenberger, Stefan; Tägil, Magnus; Tarasevičius, Šarūnas; Lidgren, Lars (Frontiers in Bioengineering and Biotechnology, 2022)
Pertrochanteric fractures (TF) due to osteoporosis constitute nearly half of all proximal femur fractures. TFs are treated with a surgical approach and fracture fixation is achieved using metallic fixation devices. Poor quality cancellous bone in osteoporotic patients makes anchorage of a fixation device challenging, which can lead to failure of the fracture fixation. Methods to reinforce the bone-implant interface using bone cement (PMMA) and other calcium phosphate cements in TFs have been described earlier but a clear evidence on the advantage of using such biomaterials for augmentation is weak. Furthermore, there is no standardized technique for delivering these biomaterials at the bone-implant interface. In this study, we firstly describe a method to deliver a calcium sulphate/hydroxyapatite (CaS/HA) based biomaterial for the augmentation of a lag-screw commonly used for TF fixation. We then used an osteoporotic Sawbones model to study the consequence of CaS/HA augmentation on the immediate mechanical anchorage of the lag-screw to osteoporotic bone. Finally, as a proof-of-concept, the method of delivering the CaS/HA biomaterial at the bone-implant interface as well as spreading of the CaS/HA material at this interface was tested in patients undergoing treatment for TF as well as in donated femoral heads. The mechanical testing results indicated that the CaS/HA based biomaterial increased the peak extraction force of the lag-screw by 4 times compared with un-augmented lag-screws and the results were at par with PMMA. The X-ray images from the patient series showed that it was possible to inject the CaS/HA material at the bone-implant interface without applying additional pressure and the CaS/HA material spreading was observed at the interface of the lag-screw threads and the bone. Finally, the spreading of the CaS/HA material was also verified on donated femoral heads and micro-CT imaging indicated that the entire length of the lag-screw threads was covered with the CaS/HA biomaterial. In conclusion, we present a novel method for augmenting a lag-screw in TFs, which could potentially reduce the risk of fracture fixation failure and reoperation in fragile osteoporotic patients.